2022
DOI: 10.12659/msm.938532
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Rebound COVID-19 and Cessation of Antiviral Treatment for SARS-CoV-2 with Paxlovid and Molnupiravir

Abstract: One of the most recently described clinical associations with SARS-CoV-2 infection is rebound COVID-19, which occurs between five and eight days following the cessation of antiviral treatment. Most case reports of rebound COVID-19 have been associated with cessation of treatment with the combined oral antiviral agent nirmatrelvir/ritonavir (Paxlovid). On 24 May 2022, the US Centers for Disease Control and Prevention (CDC) issued a Health Alert Network (HAN) Health Advisory update for patients, healthcare provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Some concerns have been recently raised on COVID‐19 rebound in patients treated with antiviral agents 38 . The COVID‐19 rebound is most frequently reported in patients taking nirmatrelvir/ritonavir agents 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Some concerns have been recently raised on COVID‐19 rebound in patients treated with antiviral agents 38 . The COVID‐19 rebound is most frequently reported in patients taking nirmatrelvir/ritonavir agents 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the in vitro antiviral activity of remdesivir, molnupiravir and nirmatrelvir have shown that they remain active against SARS-CoV-2 Omicron and other variants of concern and their target proteins (the viral RNA dependent RNA polymerase and the viral main protease Mpro) are highly conserved [31]. COVID-19 therapeutic monoclonal antibodies lost their efficacy against emerging variants due to mutations in the monoclonal antibody-targeted SARS-CoV-2 spike protein [32].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COVID-19 rebounds have been reported after cessation of Nirmatrelvir and Molnupiravir treatment, especially in patients with underlying medical conditions ( Parums, 2022 ; Wang, 2022 ). Rates of COVID-19 rebound increased for both drugs with the time after treatments.…”
Section: Direct Antivirals Available For Covid-19 Treatmentmentioning
confidence: 99%